Analisis Efektifitas Program Bantuan Permakanan Gratis terhadap Peningkatan Kesejahteraan Lansia Menggunakan T-Test One Sampel - Ratna Yuniarti; Halil Rusdi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine how the implementation of the free meal program improves the welfare of the elderly in Paokmotong Village, Masbagik District. The research method used is quantitative descriptive with a survey method. The sample consisted of 92 elderly beneficiaries of the program. Data were collected through a questionnaire and analyzed descriptively and inferentially using a one-sample t-test. The results showed that the average total welfare of the elderly was 64.58 out of a maximum score of 80, which is included in the good to very good category. The results of the t-test produced a value of t = 75.749 p-value 0.000 <0.05, which means there is a significant difference between the welfare score of the elderly and the minimum expected value. This indicates that the implementation of the free meal program has a positive impact on the quality of life of the elderly. The implementation of the free meal program has been proven to have a significant positive impact on improving the quality of life of the elderly, especially in aspects of physical and mental health and reducing their economic difficulties. This program can be a model for improving the welfare of the elderly in other areas.